Aerodynamics evaluation and flight test of a vertical take-off and landing fixed-wing UAV with joined-wing configuration in transition flight state - Baigang, Mi (Aerospace science and technology, 2024)
•A VTOL with joined-wing configuration has been designed to evaluate the transition aerodynamic performance of taking-off and landing transition modes.•A systematic simulation method based on CFD and sliding mesh is proposed to analyse the interference among the rotor, forward propeller and joined-wings, and we firstly reveal the interference mechanism with and without crosswind during the transition state of this configuration.•According to the CFD results, the transitional parameters in actual fight have been determined, and we present an actual flight to test the evaluations. The transition states between the cruising flight and the taking-off/landing process of a vertical take-off and landing (VTOL) fixed-wing UAV of joined-wing configuration are subject to significant unsteady aerodynamic interference. In this paper, the aerodynamic characteristics of this VTOL UAV during transition flights are evaluated by CFD with and without crosswind interference, in order to reveal the underlying mechanisms of the transition process. Based on these CFD-derived parameters, a flight test with a specifically-designed joined-wing VTOL UAV is proposed. The obtained results demonstrate that the forward flight speed is a crucial parameter during the takeoff transition phase. In the time interval of 5–15 s, significant disturbances are observed in the forces and moments due to the rotor deceleration and forward propeller acceleration, which result in slipstream and downwash flow effects. When crosswind disturbance is added, significant roll and yaw moments arise due to the vast vertical stabilizer area, which requires coordinated attitude adjustments between the rotor and the fixed-wing rudder surface. The descent transition phase is set a duration of 10 s. Four seconds later, as the rotor downwash flow intensifies, the lift force of the fixed wing is transferred to the rotor. When the combined lift becomes insufficient, the flight altitude decreases. When introducing crosswind disturbance, the entire aircraft undergoes significant additional pitch, yaw, and roll moments, with a maximum wave momentum greater than 200 %. Flight tests are then conducted using simulated parameters. The obtained results show that the take-off and landing transition responses without crosswinds are consistent with the predicted outcomes, which demonstrates the high effectiveness of the CFD simulations in predicting these transitions. [Display omitted]